Biomedical instrumentation applications using PSoC microcontrollers - Urbina Rojas, Wilson Fabián; Martínez Santa, Fernando; Porras, Jorge Eduardo (Visión electrónica, 2014)
This article illustrates the benefits of using PSoC microcontrollers for biomedical applications such as: electromyography (EMG), electroencephalography (EEG) and electrocardiography (ECG). The article also describes the steps to be followed for the implementation of biomedical equipment capable of capturing the different types of bio-potentials generated from the human body. These steps include: signal conditioning, filter design, signal digitalization, data communication and visualization. Finally, a low-cost electromyography device design is shown. The design easily serves as a device for either electroencephalography or electrocardiography, always using a lower amount of electronic components than regular equipment.